Association Between Pediatric Inpatient Rehabilitation Services and Children's Functional Outcomes: King Fahad Medical City Experience. (June 2020) - Madi, Sanaa Mohammed; Alraddadi, Naif Ibrahim
Background: Disability may affect children's performance of functional activities. This may translate to difficulties in returning to home and/or school. It has been documented that intensive rehabilitation programs for children with disabilities lead to an improvement in their functional abilities. Wee-FIM is a valid and reliable outcome measure that is used commonly with children undergoing rehabilitation. Objectives: To study changes in the functional status of children admitted to a specialized pediatric inpatient rehabilitation unit. Design: A retrospective cohort study. Setting: King Fahad Medical City—Rehabilitation Hospital, Riyadh, Saudi Arabia. Methods: Investigators reviewed records of children admitted to a pediatric rehabilitation unit between January 1, 2012, and December 31, 2017. The outcome measures used were rehabilitation length of stay (LOS), Wee-FIM gain, and Wee-FIM efficiency. Results: The total number of records included in this study was 361 records. Sixty percent of the children were boys. The mean age was 8.7 ± 3.8 years (range, 3-17 years). Children with cerebral palsy accounted for 45.2% of the children. The mean LOS was 43 days. Children with brain tumors had the shortest LOS compared with children with other diagnoses. Mean (SD) Wee-FIM efficiency was 0.58 (±0.6). Highest Wee-FIM efficiency was observed in children with brain tumors. Average Wee-FIM gain was 20 (±15). The highest functional gain was 27 in children with brain tumors while the lowest was 16 in children with cerebral palsy. Conclusions: Intensive inpatient rehabilitation program is associated with improvement in functional performance in children with a variety of impairments and disabilities.